The Impact of Service Quality and Accessibility of BRILink Agents on Financial Inclusion - Anang Anang; Ega Saiful Subhan; Rizky Ramadhan (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This research aims to determine the effect of Agen BRILink's service quality and accessibility on community financial inclusion, hypothesizing positive and significant partial and simultaneous impacts. Research Method: A quantitative descriptive survey was conducted with 100 purposively sampled respondents (at least 18 years old, residents, and active users) in Manggelewa Sub-district, West Nusa Tenggara. The independent and dependent variables were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3.0. Results and Discussion: Service quality and accessibility positively and significantly increase financial inclusion, both in partial and simultaneous effects. The structural model explains 68.9% of the variance in financial inclusion, with accessibility as the dominant driver, with a much larger effect size than service quality. Implications: Banks and financial authorities should prioritize rural spatial mapping for new agent placements and strengthen technical assistance to help agents maintain consistent transaction service. Originality: This study uniquely examines the effectiveness of branchless banking directly at the rural sub-district level, highlighting the interaction between geographical infrastructure barriers and grassroots financial behavior.